2017
DOI: 10.4322/2357-9730.74457
|View full text |Cite
|
Sign up to set email alerts
|

Role of advanced glycation end products in the onset of diabetic kidney disease complications

Abstract: Advanced glycation end products are known to play an important role in diabetes complications, such as diabetic nephropathy. Most known pathways of diabetic complications involve oxidative stress, that have pivotal role in cell dysfunction onset and progression of angiopathies. This review will explore how AGEs cause endothelial dysfunction in diabetes and what current biochemical mechanisms have been proposed as an explanation for the development of diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Образование КПГ Острая гипергликемия, гиперкетонемия и повышение продукции АФК на фоне ДКА инициируют неферментативное гликирование аминокислот с образованием токсичных α-дикарбонилов и, в последующем -гетерогенной группы КПГ [29,47,48]. КПГ модифицируют внутриклеточные белки, в том числе участвующие в регуляции транскрипции генов [49]. В белках в первую очередь гликированию подвергаются остатки аргинина и лизина, и одним из наиболее распространенных КПГ является N(6)-карбоксиметиллизин [47].…”
Section: основные патофизиологические механизмыunclassified
“…Образование КПГ Острая гипергликемия, гиперкетонемия и повышение продукции АФК на фоне ДКА инициируют неферментативное гликирование аминокислот с образованием токсичных α-дикарбонилов и, в последующем -гетерогенной группы КПГ [29,47,48]. КПГ модифицируют внутриклеточные белки, в том числе участвующие в регуляции транскрипции генов [49]. В белках в первую очередь гликированию подвергаются остатки аргинина и лизина, и одним из наиболее распространенных КПГ является N(6)-карбоксиметиллизин [47].…”
Section: основные патофизиологические механизмыunclassified
“…Subsequent research has suggested that AGEs also degrade pancreatic β-cells, thus contributing to their impaired function or apoptosis. Studies by Lim et al [ 35 ] showed that AGEs treatment induces ROS formation and RAGE expression, as well as causing β-cells apoptosis. Antioxidant treatment and RAGE inhibition prevented these changes, suggesting that AGEs stimulate cell death through RAGE-induced ROS generation.…”
Section: Oxidative Stress and Diabetesmentioning
confidence: 99%
“…Numerous research findings have clearly shown that these diseases and complications have a promising link with the glycated proteins and Advanced Glycation End Products (AGEs), which are formed through the protein glycation reaction under hyperglycaemic conditions in diabetes patients [ 7 ]. However, protein glycation is not a simple reaction and is defined as a series of complex non-enzymatic reactions between proteins and sugars giving rise to a multitude of heterogeneous glycated end products which are widely known as the AGEs [ 9 , 10 ]. Glycation reaction is broadly categorized into 3 stages as early-, middle-, and late-stage glycation [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%